Erasmus+ in the Eastern Partnership: Exploring International Student Mobility between Armenia and the European Union - Cairns, David (2016)
This working paper presents some initial reflections from a research project on social inclusion in international student mobility, focusing on Erasmus+ and other forms of student exchange in Armenia. Discussion starts with a brief overview of recent developments in the student mobility research field and an identification of geo-political factors that make Armenia strategically important for the European Union, and explain choice of research site. In what follows, we integrate perspectives from a workshop conducted with 45 students in Yerevan along with responses to follow-up questions, with additional perspectives provided by representatives of the Caucasus Research Resource Centre (CRRC) Armenia and Armenian Progressive Youth (APY). Considering the limited scope our research to date, this working paper is exploratory rather than a definitive statement on international student mobility to the EU in Armenia; however, in the forthcoming months we will be expanding the scope of our work, integrating emerging findings into future publications.